Expression, purification and crystallisation of DNAse and immunity proteins in the S3 pyocin of Pseudomonas aeruginosa - Newman, Christopher James (2017)
Pseudomonas aeruginosa is an opportunistic pathogen known to cause several infections such as respiratory tract infections, urinary tract infections (UTI) and sepsis. It is often associated with nosocomial infections, due to its ability to form biofilms on medical equipment such as ventilators, catheters and cannulas. P. aeruginosa produces bacteriocins that kill related strains of bacteria and have potential implications as alternative antimicrobial therapy. One such bacteriocin is the S3 pyocin, which consists of 2 proteins, a a multi domain DNAse, and an immunity protein. Comparison of the DNase domains of S3 with other S type pyocins such as pyocin S1, S2, AP41 suggested that the DNase of S3 was atypical and did not have the characteristic zinc finger binding HNH motif. The DNase/Im encoding genes were cloned into the expression vector, pET21a and the DNAse/Immunity protein complex was purified using His-Tag and gel filtration chromatography. The DNAse was then separated from the Immunity protein by protein denaturation of the complex with guanidine and the DNAse activity of pyocin S3 was confirmed by its cleavage of plasmid DNA which was inhibited by the addition of the Immunity protein. Crystallisation trials were performed, and crystals were produced in a range of conditions. A selection of high quality, large crystals returned a resolution of 1.55-1.75Å from X-ray analysis via synchrotron but lack of phase data meant that the protein structure of the DNase/Im complex is still under investigation.